2012
DOI: 10.1002/app.38668
|View full text |Cite
|
Sign up to set email alerts
|

A dynamically distributed reactor model for identifying the flow fields in industrial loop propylene polymerization reactors

Abstract: The use of distributed parameter model is becoming a common approach for simulating liquid-solid flow in loop polymerization reactors. However, there are still several issues with it. One of them is the absence of modeling of distributed pressure, as no thermodynamic state-equation is incorporated into the model. In this work, inner pressure of the reactor was associated with temperature using a thermodynamic state-equation for high-pressure liquid. The thermodynamic state-equation was solved together with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The same activation energy was used for the temperature dependence of all the kinetic coefficients of the model that is used for the analysis of the polyolefin production process using the Spheripol technology in [ 7 ]. In [ 6 ], for the temperature dependence of the kinetic coefficients , , , , a single activation energy E = 217,46 cal/mol (E/R ≈ 6245) was used, as well as in the articles [ 8 , 9 ]. Yang et al [ 6 ] concluded that the ideal mixing model (CSTR) could be used to describe the flow structure in a loop reactor of propylene polymerization at a recirculation coefficient above 50.…”
Section: Computing the Temperature Dependence Of Kinetic Parameters: ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The same activation energy was used for the temperature dependence of all the kinetic coefficients of the model that is used for the analysis of the polyolefin production process using the Spheripol technology in [ 7 ]. In [ 6 ], for the temperature dependence of the kinetic coefficients , , , , a single activation energy E = 217,46 cal/mol (E/R ≈ 6245) was used, as well as in the articles [ 8 , 9 ]. Yang et al [ 6 ] concluded that the ideal mixing model (CSTR) could be used to describe the flow structure in a loop reactor of propylene polymerization at a recirculation coefficient above 50.…”
Section: Computing the Temperature Dependence Of Kinetic Parameters: ...mentioning
confidence: 99%
“…In [ 6 ], for the temperature dependence of the kinetic coefficients , , , , a single activation energy E = 217,46 cal/mol (E/R ≈ 6245) was used, as well as in the articles [ 8 , 9 ]. Yang et al [ 6 ] concluded that the ideal mixing model (CSTR) could be used to describe the flow structure in a loop reactor of propylene polymerization at a recirculation coefficient above 50. The reactor model presented in [ 10 ] includes kinetic coefficients with activation energies of = = 12,000, = 10,000, and = = 14,000 cal/mol.…”
Section: Computing the Temperature Dependence Of Kinetic Parameters: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Luo et al modeled loop propylene polymerization reactors in bulk media. The model targeted on commercial reactor variables without paying attention to kinetics study and final product properties [21].…”
Section: Introductionmentioning
confidence: 99%